2014
DOI: 10.1017/s1355617714000812
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Structural Connectome Is Associated with Both Psychometric and Real-World Neuropsychological Impairment in Diffuse Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is likely to disrupt structural network properties due to diffuse white matter pathology. The present study aimed to detect alterations in structural network topology in TBI and relate them to cognitive and real-world behavioral impairment. Twenty-two people with moderate to severe TBI with mostly diffuse pathology and 18 demographically matched healthy controls were included in the final analysis. Graph theoretical network analysis was applied to diffusion tensor imaging (DTI) dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 46 publications
6
39
0
Order By: Relevance
“…First, we found a reduced density and an increased normalized characteristic path length in TBI patients compared with healthy controls. This finding concurs with previous research reporting reduced density and/or increased path length in both children with TBI (Caeyenberghs et al, ; Konigs et al, 2017; Yuan, Treble‐Barna, Sohlberg, Harn, & Wade, ) and adults with TBI (Caeyenberghs et al, ; Kim et al, ) in the chronic stage of recovery. Furthermore, our findings suggest an increase in normalized clustering coefficient in children with TBI.…”
Section: Discussionsupporting
confidence: 92%
“…First, we found a reduced density and an increased normalized characteristic path length in TBI patients compared with healthy controls. This finding concurs with previous research reporting reduced density and/or increased path length in both children with TBI (Caeyenberghs et al, ; Konigs et al, 2017; Yuan, Treble‐Barna, Sohlberg, Harn, & Wade, ) and adults with TBI (Caeyenberghs et al, ; Kim et al, ) in the chronic stage of recovery. Furthermore, our findings suggest an increase in normalized clustering coefficient in children with TBI.…”
Section: Discussionsupporting
confidence: 92%
“…When compared to the TC group, children with moderate/severe TBI had higher characteristic path length indicative of decreased structural integration. The current findings converge with previous studies reporting increased path length in the connectivity probability network after moderate/severe TBI in adults [Caeyenberghs et al, 2012a, 2012b, 2014; Kim et al, ] and a pilot study in children with complicated to severe TBI [Yuan et al, ]. We further extend these findings by showing that longer characteristic path length is associated with poorer neurocognitive outcome of pediatric TBI in terms of intelligence and working memory.…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancy between their findings and our results could be due to the difference in populations, that is, moderate to severe versus mTBI. Kim et al () showed no differences in transitivity and modularity between mTBI and controls, but showed longer SC characteristic path lengths were moderately correlated with worse performance on executive function and verbal learning tasks in the mTBI group. However, multiple comparisons corrections were not performed in this cross‐sectional, preliminary study.…”
Section: Discussionmentioning
confidence: 98%